Right Heart Pathology From Mechanism to Management (Springer International Publishing, 2018)
This book reviews the management of right heart diseases, incorporating etiology, physiopathology, prevention, diagnosis and treatment. The frequency of this pathology has increased in recent years, while techniques for its treatment have evolved. This book therefore represents a complete, detailed and updated presentation of this pathology, reviewing the expanded treatment options while considering the management of patients in detail. Right Heart Pathology: From Mechanism to Management provides a comprehensive insight into right heart pathology, current diagnostic methods, treatments and postsurgical management. Written by experienced cardiologists and cardiovascular surgeons who have addressed significant issues in this topic area, it represents the essential reference in this specialty.